Impact of ATP-binding cassette transporters on human immunodeficiency virus therapy - Weiß, Johanna; Haefeli, Walter E. (International review of cell and molecular biology, 2010)
Even though potent antiretrovirals are available against human immunodeficiency virus (HIV)-1 infection, therapy fails in a significant fraction of patients. Among the most relevant reasons for treatment failure are drug toxicity and side effects, but also the development of viral resistance towards the drugs applied. Efflux by ATP-binding cassette (ABC-) transporters represents one major mechanism influencing the pharmacokinetics of antiretroviral drugs and particularly their distribution, thus modifiying the concentration within the infected cells, that is, at the site of action. Moreover, drug-drug interactions may occur at the level of these transporters and modulate their activity or expression thus influencing the efficacy and toxicity of the substrate drugs. This review summarizes current knowledge on the interaction of antiretrovirals used for HIV-1 therapy with ABC-transporters and highlights the impact of ABC-transporters for cellular resistance and therapeutic success. Moreover, the suitability of different cell models for studying the interaction of antiretrovirals with ABC-transporters is discussed.